Representações sobre queimadas em livros didáticos de ciências: buscando indicadores para formação de sujeitos ecologicamente orientados. - SILVA, Camila Carneiro da (2022)
This research was developed under the intertwining of four axes: Textbooks; Content Typology; Environmental Education and training of Ecological Subjects. Each of these themes represents distinct conceptions, which in an integrated way can present a new approach and a specific meaning, as a teaching proposal. Thinking about the formation of Ecological Subjects implies discussing about the ecological movements that emerged in the mid-1960s (CARVALHO, 2002; 2012), how these events contributed to discuss such an important agenda and that can integrate methodologies, postures, knowledge, claims related to environmental crises, as well as to seek new ways of accessing reality through education. It is from these conceptions that we understand how Environmental Education has a fundamental role to dialogue about the projection of the term and the need for the formation of an Ecological Subject. In this context, we think of situations present in the daily life of students, such as Queimadas, since they appear as a theme that contemplates the crossing of the realities and different fields of study, being a routine but not homogeneous activity and that, before being taken as a harmful practice to the environment, is based on historical and cultural factors that result in different interpretations (CARCARÁ; MOITA NETO, 2012). And, thinking of adding factors specific to the reality of elementary school students, we consider textbooks as a safe source to dialogue about the importance of developing competencies that allow us to know and read reality in a critical and contextualized way. For this, we comment on the type of Content that is adopted in the books, in order to identify the attributions given for the different environmental contents and contexts, as well as the intentions adopted to describe such contexts (COLL et al., 1992). To this end, in this research, we seek to identify and characterize the different contents that refer to Environmental Education in Science Textbooks adopted in public schools in the city of Timbiras, Maranhão, in order to obtain an overview of environmental issues, to later work on contents on Queimadas, taking it as a practice that affects the city every year under various factors, from cultural to economic, social and political. Therefore, we seek to reveal the types of Conceptual, Procedural or Aitudinal Content as a possibility to develop competencies for the formation of Ecological Subjects. In addition, our methodological approach followed the perspective of qualitative research (BOGDAN; BIKLEN, 1996), with the documentary and exploratory approach to delineate data collection, which were treated, characterized, systematized and described. Our discussion followed the trend of the Discursive Textual Approach (MORAES; GALIAZZI, 2006), dialoguing about the phenomena that we identify and that we put into debate. In our analysis, we identified that the contents express different configurations and typologies, however, we noticed that the Conceptual typology is in relation to the others, but all appear, thus, we reflect on how the typologies of content can influence the and formation of ecologically oriented subjects, in a perspective full of awareness in relation to environmental problems, by allowing the support of new meanings and values, beliefs and ways of knowing and understanding the events of the world and about themselves, a construction that we understand is not explicit in textbooks, but which suppose an intentionality of those who read it, which can be developed and grounded from the foundations of Environmental Education and ecological movements.